2012
DOI: 10.4103/0976-237x.107440
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors affecting post-obturation pain following single visit root canal treatment in Indian population: A prospective, randomized clinical trial

Abstract: Aim:This prospective randomized clinical study (1) investigated the prevalence of post-obturation pain after single visit root canal treatment and (2) evaluated the influence of factors affecting the pain experience.Materials and Methods:One thousand three hundred and twenty eight (1328) patients were included in this study. Conventional single visit root canal treatment was carried out. The chemicomechanical preparation of root canals was done by a rotary protaper system with a combination of hand instruments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 12 publications
8
65
1
2
Order By: Relevance
“…Preoperative pain has been shown to have a significant influence on postoperative pain (Walton & Fouad , Ali et al . , Nixdorf et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative pain has been shown to have a significant influence on postoperative pain (Walton & Fouad , Ali et al . , Nixdorf et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Teeth with irreversible pulpitis were selected in this study to reduce the risk of exacerbation by residual microorganisms found in teeth with necrotic pulp, teeth with apical periodontitis or re-treatment cases (10) . Moreover, mandibular posterior teeth were selected due to higher incidence of pain in comparison with maxillary anterior teeth because of the mandibular dense trabecular pattern, that reduces the blood flow and causes localization of infection and exudates leading to delayed healing patterns (11) .…”
Section: Results:-mentioning
confidence: 99%
“…In this study; the old filling was removed using combination of Gates Glidden with Hedstrom files and GP solvent as needed. This technique was reported to be effective in several in vitro and clinical studies (27,28).…”
Section: Discussionmentioning
confidence: 99%